Optimising plant layout decisions based on emulation models – technical framework and practical insights. (1st January 2013) - Schoech, Robert; Schmid, Susanne; Hillbrand, Christian; Fleisch, Ruth
Planning, implementation, and operation of cut-to-size plants are very costly and time-consuming processes. Due to various possible combinations of plant building blocks and because each plant is designed as a uniquely customised system, the complexity of these plants can be enormous. Hence, the decisions to be taken within the planning process very often exceed human cognitive limits. Therefore, this paper describes a decision supporting approach based on discrete event simulation, which enables the planner to model, emulate, simulate, and animate the plant processes. This in turn facilitates exact forecasts of the attainable performance. Based on the proposition of a generic system architecture for this decision support system (DSS), we provide possible solutions for processing of control system orders and task handling in the simulation environment. These mechanisms have been implemented and validated. This article describes a case study of the designed DSS within the plant planning process at a large German kitchen manufacturer. Finally, we discuss the opportunities arising from this approach as well as its future potential.